Building Dharma-Based Social Infrastructure: The Urgency of Hindu Philanthropy in Alleviating Social Inequality - Irawan, I Ketut Angga; Suda, I Ketut; Wirawan, Komang Indra (International Journal Labs, 2025)
The development of social infrastructure plays a critical role in enhancing societal welfare and reducing social disparities. In Indonesia, particularly in Bandar Lampung, the contribution of religious and cultural values—such as Dharma and Hindu generosity—remains underexplored in shaping sustainable social infrastructure. This study aims to investigate how Hindu charitable practices, including dana punia (donations), cooperative initiatives, and seva (selfless service), influence the development of social infrastructure and to propose a structured framework for integrating these practices into long-term planning. A qualitative research design was employed, combining in-depth interviews with community leaders, participatory observation, and document analysis. Data were analyzed using descriptive-analytical and thematic techniques to identify key patterns and challenges. The findings indicate that Hindu generosity significantly supports the construction and maintenance of social infrastructure, yet these efforts are often intermittent, informal, and lack coordination. Based on Dharma principles, the study proposes a systematic framework that aligns traditional charitable practices with organized, sustainable, and scalable social infrastructure development. This framework has the potential to enhance the impact of community-led initiatives, encourage consistent participation, and guide policymakers and religious organizations in designing programs that strengthen social cohesion and welfare.